Anthropometric Measurements of the Forearm and their Correlation with the Stature of Bengali Adult Muslim Females (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):377-81The abstract of this article is available on the PubMed website